Comparative study on shear failure behavior of squat high-strength steel reinforced concrete shear walls with various high-strength concrete materials. (February 2020) - Hung, Chung-Chan; Hsieh, Ping-Lun
Abstract: The shear failure behavior of four squat shear walls with high-strength steel (HSS) and high-strength concrete (HSC) was experimentally investigated in this study. The experimental variables are the steel grade, namely SD420 and SD785, and the type of HSC materials, namely commercially available HSC with the inclusion of steel fibers and ultra-high performance concrete (UHPC) with or without steel fibers. The squat walls were tested under displacement reversals and their cyclic responses were extensively compared using various performance measures. The results indicate that the addition of steel fibers in the squat walls transformed the shear critical damage pattern from significant concrete spalling to localized diagonal cracks. The HSS reinforced squat wall made using commercially available HSC with the addition of a 0.75% volume fraction of steel fibers had a load-displacement response, energy dissipation capacity, and shear strength comparable to those of the squat walls made using specially mixed UHPC containing a 1.5% volume fraction of steel fibers. Moreover, while the high-strength horizontal reinforcement in the squat non-fiber HSC did not yield until the end of the test, its yield strength was fully utilized when it was used in the fiber-reinforced HSC walls. In addition to the experimental study, the applicability of existing design codes and the softened strut-and-tie model for assessing the shear strength of the high-strength squat walls was evaluated.